1999
DOI: 10.1128/jvi.73.2.930-938.1999
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric Plant Virus Particles Administered Nasally or Orally Induce Systemic and Mucosal Immune Responses in Mice

Abstract: The humoral immune responses to the D2 peptide of fibronectin-binding protein B (FnBP) of Staphylococcus aureus, expressed on the plant virus cowpea mosaic virus (CPMV), were evaluated after mucosal delivery to mice. Intranasal immunization of these chimeric virus particles (CVPs), either alone or in the presence of ISCOM matrix, primed CPMV-specific T cells and generated high titers of CPMV-and FnBP-specific immunoglobulin G (IgG) in sera. Furthermore, CPMV-and FnBP-specific IgA and IgG could also be detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(22 citation statements)
references
References 46 publications
2
19
0
1
Order By: Relevance
“…Oral immunization was considerably less effective, with only serum antibody being stimulated in a minority of mice. Similar results were obtained when mice were immunized nasally or orally with a CPMV chimera expressing a 30-amino acid sequence from the S. aureus FnBP (Brennan et al, 1999d). Detailed characterization of the immune responses in mice immunized nasally with CPMV chimeras expressing epitopes from CPV provided further support to the idea that it will be possible to stimulate mucosal immunity by this route (Nicholas et al, 2002).…”
Section: Mucosal Immunizationsupporting
confidence: 64%
“…Oral immunization was considerably less effective, with only serum antibody being stimulated in a minority of mice. Similar results were obtained when mice were immunized nasally or orally with a CPMV chimera expressing a 30-amino acid sequence from the S. aureus FnBP (Brennan et al, 1999d). Detailed characterization of the immune responses in mice immunized nasally with CPMV chimeras expressing epitopes from CPV provided further support to the idea that it will be possible to stimulate mucosal immunity by this route (Nicholas et al, 2002).…”
Section: Mucosal Immunizationsupporting
confidence: 64%
“…We achieved this result by intranasally delivering empty virus-like particles (VLPs), which act to modulate the lung microenvironment, and harness and focus immune responses. Recent exploration in the utilization of nanoparticles [12][13][14], virus-like particles [15][16][17][18][19][20][21], and viruses which have no mammalian cell tropism, has shown that these platforms are naturally immunostimulatory, and likely utilize evolutionarily conserved cell surface receptors, thereby safely engaging immune signaling pathways without replicating [22][23][24][25][26]. Furthermore, many of these strategies are currently on the market or undergoing clinical trials, and have already had broad global impact in safely preventing disease [21,[27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…The capability of CVPs in inducing an antibody response specifically to the displayed epitope upon intranasal, intraperitoneal or oral administration, have been extensively demonstrated in different animal models (Table 1). Other data show CVPs ability to elicit a strong specific neutralizing immune response in the absence of adjuvants (Yusibov et al, 1997; Brennan et al, 1999; Marusic et al, 2001). Oral delivery of spinach leaves infected with CVPs elicited a strong antibody response to the displayed rabies virus peptide in mice and human volunteers (Yusibov et al, 2002), indicating a potential use of this system as a supplementary oral booster for rabies vaccinations.…”
Section: Plant Viral Vectorsmentioning
confidence: 94%